Avaliação de projetos de mineração utilizando a teoria das opções reais em tempo discreto: um estudo de caso em mineração de ferro - Pessoa, Gerisval Alves (2006)
The study of the Real Options Theory (ROV) that incorporates to the project valuation, the growth options and the managerial flexibilities that it's due to the existent uncertainties in the environment in which the companies operate. Approaches the investments analysis traditional methods based in the discounted cash flow (DCF), it detaches their advantages and limitations; the real options theory showing their advantages in relationship to the traditional methods; and a case study. It has as main objective to present that the real options theory is viable and complementary to the investments analysis traditional method in the iron ore industry, with the approach of the evaluation in discreet time method. This method allows specifying the analysis problem and to solve it with the use shelf decision analysis software in a simpler way and more intuitive solution than the traditional methods of real options valuation and it provides greater flexibility in the modelling of problem. The modeling of the real options inherent in the projects bases on the use of binomial decision analysis tree to model the stochastic processo The evaluation is accomplished in four steps in agreement with the methodology proposed by Copeland and Antikarov (2001) and Brandão and Dyer (2005): modeling of the basic assets, in other words, calculation of the net present value without flexibility; creation of the binomial model using the software to model the basic assets, computing the neutral probabilities and risks; modeling the real options inherent in the project; and resolution of the binomial tree, in other words, analysis of the real options. The results show that it's possible to implement this approach in evaluation projects in the iron ore industry.